Core java programming : a practical approach - Kute, Tushar B. (New Delhi, India : University Science Press, 2016)
The book is a special guide to all who want to learn the Java Programming from basic without the knowledge of programming languages like C or C++. It covers on extensive syllabus designed by Maharashtra State Board of Technical Education for 'Java Programming' of Computer Engineering group (CO/CM/IF/CD/CW) for semester V. The illustrative and demonstrative programs on each topic with 144 solved programming examples are covered in the book. It has a comprehensive coverage of complicated topics like packages, interfaces and streams with detailed description of multithreaded programming with real life problems solution. The objective questions and programming exercises of each chapter are given at the end. More than 300 questions to solve including programming exercises with 100% Practical Implementation of all the topics on Core Java Programming are covered in it.
Chapter 1. Introduction to Java -- Chapter 2. Classes, objects and methods -- Chapter 3. Arrays, strings and vectors -- Chapter 4. Packages and interfaces -- Chapter 5. Exceptions and multithreading -- Chapter 6. Apples and graphics programming -- Chapter 7. Streams of file I/O -- Appendix -- Index.
Includes bibliographical references and index.
Keywords: OBJECT-ORIENTED PROGRAMMING (COMPUTER SCIENCE)